Bevacizumab combined with re-irradiation in recurrent glioblastoma - She, Lei; Su, Lin; Liu, Chao (Frontiers in Oncology, 2022)
Background: Glioblastoma is characterized of rich vasculature, abnormal vascular structure and function. Currently, there is no standard treatment for recurrent glioblastoma (rGBM). Bevacizumab (BEV) would improve tumor microenvironment by inhibiting the neovascularization, alleviating the hypoxia condition in the tumor area and activating the immune microenvironment. BEV may exert synergistic effects with re-irradiation (re-RT). Purpose: The purpose of this study was to identify the safety, tolerability, and efficacy of a combined treatment of BEV with re-RT in rGBM. Methods: In this retrospective study, all the enrolled patients experienced at least one event of recurrence and at least one surgical pathologically confirmed glioblastoma. All patients were treated with re-RT in combination with BEV. BEV was administered until progression or serious adverse events. Results: A total of 26 rGBM patients were enrolled in this study. After a median follow-up of 21.9 months, the median progression-free survival (PFS) was 8.0 months (95% confidence interval (CI): 6.5-9.5 months), the 6-month PFS rate was 65.4%, and the 1-year PFS rate was 28.2%. The median overall survival (OS) was 13.6 months (95% CI: 10.2-17.0 months),the 6-month OS rate was 92.3%, and the 1-year OS rate was 67.5%. The patient showed good tolerance during the treatment, > 3 grade side event had not occurred. The occurrence rate of radiation necrosis was 0%. Combined treatment of gross total resection (GTR) before re-RT and concurrent temozolomide during the re-RT was an independent prognostic factor that affected both OS and PFS in the whole cohort (OS: 0.067, 95% CI: 0.009-0.521, P = 0.010; PFS: 0.238, 95% CI: 0.076-0.744, P = 0.038). Conclusion: Re-RT combined with concurrent and maintenance BEV treatment was safe, tolerable and effective in rGBM patients. Moreover, GTR before re-RT and selective concurrent temozolomide would further improve the PFS and OS.